Pembuatan Konten Promosi Produk Siswa Menggunakan Smartphone (Altruism: The Indonesian Journal of Community Engagement, 2024)
The development of digital technology, particularly the use of smartphones, has provided significant opportunities for product marketing activities. However, limited skills in creating engaging promotional content remain a barrier for students in developing their businesses. This community service activity aims to improve students' skills in creating product promotional content using smartphones as a simple and effective digital marketing medium. The methods used included outreach, training in simple photography and videography techniques, and hands-on practice in creating promotional content. The results of the activity demonstrated improved student skills in producing engaging visual content, an increased understanding of digital promotional strategies, and increased student interest in developing digital-based businesses. This program contributes to the development of students' digital literacy and entrepreneurship.
Keywords: Promotional Content; Smartphone; Digital Marketing